2012 IEEE Haptics Symposium (HAPTICS) 2012
DOI: 10.1109/haptic.2012.6183839
|View full text |Cite
|
Sign up to set email alerts
|

Composing vibrotactile music: A multi-sensory experience with the emoti-chair

Abstract: The Emoti-Chair is a novel technology to enhance entertainment through vibrotactile stimulation. We assessed the experience of this technology in two workshops. In the first workshop, deaf film-makers experimented with creating vibetracks for a movie clip using a professional movie editing software. In the second workshop, trained opera singers sang and 'felt' their voice through the Emoti-Chair. Participants in both workshops generally found the overall experience to be exciting and they were motivated to use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…Further investigation into differences between discrete and continuous vibrotactile beats may be a topic of interest for future research. In any case, the ability of the deaf group to synchronize to a vibrotactile beat validates the use of vibrotactile music technology for people with hearing impairments (e.g., Karam et al, 2009 ; Baijal et al, 2012 ), and this finding may help guide future developments in this field, particularly with regards to interventions for social dancing.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Further investigation into differences between discrete and continuous vibrotactile beats may be a topic of interest for future research. In any case, the ability of the deaf group to synchronize to a vibrotactile beat validates the use of vibrotactile music technology for people with hearing impairments (e.g., Karam et al, 2009 ; Baijal et al, 2012 ), and this finding may help guide future developments in this field, particularly with regards to interventions for social dancing.…”
Section: Discussionsupporting
confidence: 62%
“…Deaf people often participate in social dancing situations (Darrow, 1993 ), but little research has examined this behavior. In this population, music is typically experienced through vibrations, as evidenced by the development and effectiveness of vibrotactile platforms for musical experiences in the deaf (Karam et al, 2009 ; Baijal et al, 2012 ). In terms of beat synchronization, one recent study demonstrated that early deaf people are able to synchronize a hand-tapping motion to a visual stimulus, and in fact, perform better than hearing people when the stimulus is discrete (a flashing dot) rather than continuous (a bouncing ball) (Iversen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal systems allow the construction of interactive environments in which users can use different senses and carry out play activities that contribute to their psychomotor development [68,69,70,71]. This case can be clearly seen in [58,61] where the created devices involved different feedback, such as haptic and visual cues, that allowed the patient to perceive the information through multiple senses and react to the stimuli, causing the activity to be more engaging.…”
Section: Discussionmentioning
confidence: 99%
“…Deaf individuals report that vibrotactile devices, such as haptic chairs, are a significant contribution to their musical enjoyment [ 72 ]. Using vibrotactile technology, music has been created in which vibrotactile aspects supersede the auditory aspects of music [ 73 ]. Research has shown that incorporating additional vibrotactile stimuli though sensory substitution technology may be an effective way to convey the emotional information when experiencing music [ 74 , 75 ].…”
Section: Non-auditory Elements Of Music and The Deaf Experiencementioning
confidence: 99%